Cool girl aesthetic in British culture: historical conditions and the case of i-D = Cool girl aesthetic trong bối cảnh văn hóa nước Anh: những điều kiện lịch sử tạo thành và câu chuyện về i-D - Bùi, Thu Uyên (ĐHQGHN - Trường Đại học Ngoại ngữ, 2021)
This thesis is a humanities-oriented research that explores a cultural phenomenon called Cool girl aesthetic that arose in the British postcolonial youth scene and the particular case of i-D, an influential London-based fashion magazine, as an example of a specific space that nurture and contribute to the development of the phenomenon. It studies Cool girl aesthetic as both the total set of meanings and senses that constitute Cool girl and the stylistic manifestation of Cool girl. Borrowing the theoretical perspective that Jacques Rancière specifies with the conceptual formulation “the distribution of the sensible,” this thesis examines the network of events, meanings and senses that make Cool girl aesthetic sensible, particularly in the ways girls navigate through Cool and subcultural spaces. This is achieved through analyzing a series of historical events taking place in Cool and subcultural spaces to reveal patterns and characteristics that dictate Cool girl aesthetic, especially in the British postcolonial subcultures where social, political, and economical changes along with the rise of second and third wave feminism gave rise to the emergence of Cool girl aesthetic as an adaptive strategy in the originally pure male stratagem of Cool. This thesis reveals the core of Cool girl aesthetic to be a complex and dynamic struggle to balance between the predominantly masculine Cool codes and the tensions and rules brought forth by the hegemonic femininity. i-D is brought in as a visual illustration of how a specific entity participates in and makes meaningful contribution to the broad networks of meaning and sense that support Cool girl aesthetic by creating its own unique expressions and practices.